ANALISIS PEMBELAJARAN DARING KELAS XI IPS-1 PADA MATA PELAJARAN GEOGRAFI SMA NEGERI 3 SOLOK - Hermandi, Rizka Angreilyn; Anwar, Syafri (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
Rizka Angreilyn Hermandi. ANALYSIS OF ONLINE LEARNING CLASS XI IPS-1 IN GEOGRAPHY, Thesis, Padang: Faculty of Social Sciences, Padang State University, 2022. This study aims to (1) identify the online learning process in XI IPS-1 at SMA 3 Solok and (2) identify the cause of online learning in class XI IPS-1 is better than other classes. This type of research is descriptive qualitative research informants, namely students of SMA Negeri 3 Solok class 11 IPS-1. The sampling technique was carried out using the Total Sampling technique. Data collection techniques used are interview techniques and observation techniques. The data analysis technique used is analysis based on the data obtained, reduced, presented and verified. Based on the research results that have been obtained (1) The online learning process carried out in class XI IPS-1 SMAN 3 Solok was successfully carried out because online learning had been carried out during a pandemic situation and when face-to-face learning became a new innovation for better learning. (2) The cause of the success of online learning in class XI IPS-1 SMAN 3 Solok is due to the role of parents in fully supporting the times and progress of education, having online learning tools with good network quality and student motivation in learning as evidenced by seeking additional material other than the material provided by the teacher.